The collapse : the accidental opening of the Berlin Wall - Sarotte, Mary Elise, 1968- 1968- (Basic Books, 2014)
"In The Collapse historian Mary Elise Sarotte shows that the opening of the Berlin Wall on November 9, 1989, was not, as is commonly believed, the East German government's deliberate concession to outside influence. It was an accident. A carelessly worded memo written by mid-level bureaucrats, a bumbling press conference given by an inept member of the East German Politburo, the negligence of government leaders, the bravery of ordinary people in East and West Berlin...these combined to bring about the end of nearly forty years of oppression, fear, and enmity in divided Berlin. Drawing on evidence from archives in multiple countries and languages, along with dozens of interviews with key actors, The Collapse is the definitive account of the event that brought down the East German Politburo and came to represent the final collapse of the Cold War order"